Implementation of gender equality in social studies learning processes at Junior High Schools in Kedawung District, Cirebon Regency - Fajriyati, Anissa; Astuti, Tri Marhaeni Pudji; Lestari, Puji (Journal of Educational Social Studies, 2024)
This research employs a qualitative approach with a gender perspective and gender pathway analysis. Data were gathered through observation, interviews, documentation, and triangulation. The data analysis technique involves four stages: data collection, data condensation, data presentation, and drawing conclusions. Through this approach, teachers have successfully created a learning environment that promotes gender equality and provides all students with the opportunity to learn and develop without being constrained by stereotypes or gender discrimination. The implementation of gender equality in Social Studies learning at Junior High Schools can bring several positive aspects. Potential findings include increased student participation regardless of gender, improved learning outcomes through the integration of gender perspectives, the formation of gender awareness, changes in attitudes and social norms, as well as better involvement from parents and the community. The learning environment fosters conditions that support student development without gender barriers, and the implementation of gender equality in Social Studies learning at Junior High Schools demonstrates positive potential in several aspects of learning.